SnS2 quantum dots uniformly anchored on dispersed S-doped graphene as high-rate anodes for sodium-ion batteries. Issue 10 (July 2020) - Jin, Shibo; Sun, Xiaohong; Cai, Shu; Guo, Jinze; Fan, Anran; Zhang, Na; Wu, Han; Zheng, Chunming
Abstract: SnS2 stands out to be a potential anode material for sodium-ion batteries (SIBs) owing to its high theoretical capacity and earth abundance. Nevertheless, the severe volume expansion and aggregation of SnS2 would lead to low reversible capacity and poor rate capability. Herein, SnS2 quantum dots uniformly anchored on dispersed S-doped graphene were designed and synthesized via a simple hot bath process with the addition of K + (K-SnS2 @SG). Dispersed S-doped graphene can not only increase the electric conductivity and mitigate the large volume expansion, but also accelerate the electronic/ionic transportation and improve the electrochemically active sites for Na + storage. Uniformly distributed SnS2 quantum dots can shorten the transfer and diffusion path of Na + /electrons, and the abundant voids around quantum dots can relieve much of volume expansion and keep SnS2 from aggregating. Accordingly, the K-SnS2 @SG electrode delivers a high reversible capacity (743 mAh g −1 at 45 mA g −1 ) and superior rate capability (236 mAh g −1 at 27 A g −1 ). Furthermore, the kinetic analyses demonstrate that the dominant capacitive behaviors account for excellent rate capability.